Origins and functional differences of blood endothelial cells - Ng, Chun Yi (2023)
The interests in blood endothelial cells arise from their therapeutic potential in vascular repair and regeneration. Our understanding of blood endothelial cells that exist in the circulation has been evolving significantly from the original concept of endothelial progenitor cells. Many studies have uncovered heterogeneities of blood endothelial subtypes where some cells express both endothelial and hematopoietic antigens, and others possess either mature or immature endothelial markers. Due to the lack of definitive cell marker identities, there have been momentums in the field to adopt a technical-oriented labeling system based on the cells' involvement in postnatal neovascularization and cell culture derivatives. Our review streamlines nomenclatures for blood endothelial subtypes and standardizes understanding of their functional differences. Broadly, we will discuss about myeloid angiogenic cells (MACs), endothelial colony-forming cells (ECFCs), blood outgrowth endothelial cells (BOECs) and circulating endothelial cells (CECs). The strategic location of blood endothelial cells confers them essential roles in supporting physiological processes. MACs exert angiogenic effects through paracrine mechanisms, while ECFCs are recruited to sites of vascular injury to participate directly in new vessel formation. BOECs are an in vitro derivative of ECFCs. CECs are shed into the bloodstream from damaged vessels, hence reflective of endothelial dysfunction. With clarity on the functional attributes of blood endothelial subtypes, we present recent advances in their applications in disease modelling, along with serving as biomarkers of vascular tissue homeostasis.